Action research for energy system transformation. Issue 4 (8th August 2022) - Jorgenson, Simon; Stephens, Jennie C.
ABSTRACT: Responding to the climate crisis requires a large-scale transformation of energy systems away from fossil fuels toward a more distributed, equitable, renewable-based society. The societal benefits of this transformation which could redistribute power, literally and figuratively, go well beyond decarbonization; a renewable society could also be a healthier, more economically just society. This study conceptualizes action researchers as key drivers of these systemic change processes. We argue that transforming and democratizing energy systems should be the focal point of action researcher's efforts to address climate change. To advance this argument, the study draws on the systemic action research, energy democracy, and sustainability transitions literature and includes recommendations, examples, and practical suggestions for conducting energy-related action research. This study's findings will be useful to researchers interested in engaging the climate crisis by building transformative capacity in the context of local and regional energy systems.